Understanding protein arginine methyltransferase 1 (PRMT1) product specificity from molecular dynamics. Issue 20 (15th October 2016) - Gathiaka, Symon; Boykin, Brittany; Cáceres, Tamar; Hevel, Joan M.; Acevedo, Orlando
Graphical abstract: Abstract: Protein arginine methyltransferases (PRMTs) catalyze the post-translational methylation of specific arginyl groups within targeted proteins to regulate fundamental biological responses in eukaryotic cells. The major Type I PRMT enzyme, PRMT1, strictly generates monomethyl arginine (MMA) and asymmetric dimethylarginine (ADMA), but not symmetric dimethylarginine (SDMA). Multiple diseases can arise from the dysregulation of PRMT1, including heart disease and cancer, which underscores the need to elucidate the origin of product specificity. Molecular dynamics (MD) simulations were carried out for WT PRMT1 and its M48F, H293A, H293S, and H293S-M48F mutants bound with S -adenosylmethionine (AdoMet) and the arginine substrate in an unmethylated or methylated form. Experimental site-directed mutagenesis and analysis of the resultant products were also performed. Two specific PRMT1 active site residues, Met48 and His293, have been determined to play a key role in dictating product specificity, as: (1) the single mutation of Met48 to Phe enabled PRMT1 to generate MMA, ADMA, and a limited amount of SDMA; (2) the single mutation of His293 to Ser formed the expected MMA and ADMA products only; whereas (3) the double mutant H293S-M48F-PRMT1 produced SMDA as the major product with limited amounts of MMA and ADMA. Calculating the formation of near-attack conformers resembling SN 2 transition states leading to either the ADMA or SDMA products finds that Met48 and His293 may enable WT PRMT1 to yield ADMA exclusively by precluding MMA from binding in an orientation more conducive to SDMA formation, i.e., the methyl group bound at the arginine Nη2 position.